Representasi Budaya Jepang Aisatsu dalam Anime Spirited Away - Destria, Wanda; Arfianty, Rani (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2024)
The anime film Spirited Away is an anime that tells the story of Chihiro Ogino, a 10 year old girl who, when she moves to a new neighborhood, enters the world of kami (Japanese Shinto spirit folklore). After her parents were turned into pigs by the witch Yubaaba (Natsuki), Chihiro took a job at Yubaaba's bathhouse to find a way to free herself and her parents, and return to the human world. The depiction of Japanese aisatsu culture is in the anime film Spirited Away which includes Aisatsu Introduction When First Meeting, Aisatsu Says Thank You, Aisatsu Based on Time, Aisatsu to the Person Who is Going, Aisatsu When Getting Food, Aisatsu When leaving and Aisatsu apologizing, some of these scenes depict Japanese culture aisatsu.